Experiments on confidence calibration and decision making - Murad, Zahra (2015)
This thesis reports on three experiments studying subjects' confidence about performance on a task and how it relates to decision-making under uncertainty. Chapter 1 introduces the thesis providing an overview of the common themes and methods underlying this research.